2007
DOI: 10.1007/s10535-007-0068-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microwave treatment on growth, photosynthetic pigments and some metabolites of wheat

Abstract: Wheat (Triticum aestivum L. Sakha 61) grains were exposed to microwave radiation of a wavelength 2.85 cm and frequency 10.525 GHz for 15, 45, or 75 min. The exposed grains were germinated and then harvested after 7 and 14 d. While 15-and 45-min exposure of the grains stimulated seedling shoot length and fresh and dry masses, the exposure for 75 min had no pronounced effects. 15 and 75-min irradiation increased succulence and pigment contents in 7-and 14-d-old seedlings. While the ratios chlorophyll (Chl) a/b, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…Seed irradiation did not influence the amount of photosynthetic pigments in radish seedlings FM. Positive effect of HPM on photosynthetic pigment amount in wheat seedlings was reported by Hamada (2007). He admitted that chlorophyll a/b and carotenoids ratios increased in 7 days' old seedlings, but they tended to diminish in 14 days' old seedlings as compared with non-irradiated seedlings.…”
Section: Results and Analysismentioning
confidence: 88%
See 2 more Smart Citations
“…Seed irradiation did not influence the amount of photosynthetic pigments in radish seedlings FM. Positive effect of HPM on photosynthetic pigment amount in wheat seedlings was reported by Hamada (2007). He admitted that chlorophyll a/b and carotenoids ratios increased in 7 days' old seedlings, but they tended to diminish in 14 days' old seedlings as compared with non-irradiated seedlings.…”
Section: Results and Analysismentioning
confidence: 88%
“…Other scientists found that direct effect of electromagnetic fields stimulates the development of tomato plants, irradiated tomato sprouts grew up higher, formed more leaves and accumulated more fresh mass (Stašelis et al, 2004). Hamada (2007) investigated different doses of microwaves on wheat and determined that irradiation increased root and shoot lengths also fresh mass in 14 days' old wheat seedlings.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this increase was positively correlated with the microwave power [Łupinska et al, 2009;Han, 2010]. The protein and amino acid contents of wheat seedlings increased when the seeds were pretreated with microwaves, and the increase was microwave irradiation dose-dependent [Hamada, 2007]. The dose-dependency may be related to the changes in the protein structure of the enzyme due to the microwave treatment [Damm et al, 2012].…”
Section: Introductionmentioning
confidence: 93%
“…Br. ), parthenium (Parthenium hysterophorus L.) and bellyache bush (Jatropha gossypiifolia L.) [36] Effects of microwave treatment on growth, photosynthetic pigments and some metabolites of wheat [66] Microwave seed treatment reduces hardseededness in Stylosanthes seabrana and promotes redistribution of cellular water as studied by NMR relaxation measurements [67] Effect of microwave fields on the germination period and shoot growth rate of some seeds [68] Germination of Chenopodium album in Response to Microwave Plasma Treatment [69] Work conditions for microwave applicators designed to eliminate undesired vegetation in a field [70] microwave treatment (Figure 7), Khan et al [72] demonstrated that immediately after microwave soil treatments, the relative abundance of Firmicutes increased while the relative abundance of Proteobacteria decreased significantly. They also showed that the relative abundances of beneficial soil microbes (Micromonosporaceae, Kaistobacter and Bacillus) were significantly higher, as soils recovered from high heating intensities induced by microwave soil treatment, compared with untreated soils.…”
Section: Paper Title Referencementioning
confidence: 99%